دراسة مسألة الدفع الجانبي للتربة المفككة على الجدران الاستنادية بمساعدة طريقة العناصر المحددة - منذر عمران (Tishreen University, 2019)
تعتبر طريقة العناصر المحددة من الطرق المفيدة في حل المسائل الجيوتكنيكية المعقدة كما أنها من الطرق التي لاتزال تشهد انتشارا واسعا لارتباطها المباشر بالحاسوب ولقدرتها على حساب الاجهادات والتشوهات بشكل دقيق في مختلف نقاط المنشأة المدروسة. إن مسألة الدفع الجانبي للتربة المفككة على الجدران الاستنادية بالعلاقة مع احتكاك الجدار بالتربة ومع قيم وأشكال انزياح ودوران الجدار هي مسألة لم تحل بعد بشكل كامل وقد تم في هذا البحث دراسة الدفع على الجدران الاستنادية في حالات مختلفة من الدوران والانزياح كما درست الحالات الاجهادية والسلوك التشوهي بالارتباط مع الشروط الطرفية وتم اختيار قانون مناسب للمادة يعبر عن العلاقة بين الاجهادات والتشوهات. ومن اجل الحل جرى تصميم برنامج حسابي واستخرجت قوانين المادة من تجارب الثلاثي المحاور واختير قانون المادة الذي يعطي القيم الأقرب لنتائج القياس على الموديل المجرب وجرى تقسيم النموذج الى شبكة مناسبة من العناصر المحددة تراعي الشروط الطرفية. بينت النتائج أن الدفع الجانبي الفعال يحدث في حالة الانزياح المتوازي عند انزياح مقداره 0,002H (حيث H ارتفاع الجدار) وعند انزياح مقداره 0,004H في حالة دوران الجدار حول قاعدته وعند انزياح مقداره 0,005H لحالة الدوران حول الراس مهما كانت قيمة زاوية احتكاك التربة بالجدار. كما اظهرت النتائج تطابقا مقبولا مع القيمة النظرية لحالة الدفع اثناء السكون وكذلك تطابقا مقبولا نسبيا لمسارات الاجهاد التابعة للتجارب والقيم المحسوبة لاغلب الحالات المحسوبة. تبين النتائج أن سطح الانزلاق الناتج في جميع الحالات هو غير خطي وهذا مايخالف تقريب كولومب وقد تم التوصل إلى صيغ تقريبية لحساب الدفع الجانبي على الجدران الاستنادية وفقا لحالة انزياحها. The method of finite elements is useful in solving complex geo-technique  problems. It is still widely used because of its dependence on computer and its ability to calculate accurate stress and deformation in all points of the structure. Lateral pressure of soil on retaining walls together with the friction of wall with soil as well as the values and forms of displacement and rotation of wall, is as yet an unsolved problem. In this paper we study the pressure of soil on the retaining wall in different cases of displacement and rotation as well as the stress cases and deformation act in relation with end condition, by selecting a suitable law express the relation between stress and deformation. For the solution we have designed a calculation program to find out the law of substance from the experiments of three axes. Then we selected the substance law which gives the nearest values to the results of measurement on tested model which has been divided to a suitable net of finite elements in accordance with the end conditions. The results show that the active Lateral pressure happens in the case of parallel displacement at a value of displacement that equals 0,002H (where H is the height of wall), and at a displacement that equals 0,004H in the case of wall rotation about its base, and at a displacement that equals 0,005H in the case of rotation about the head for all values of friction angle of soil with the wall. Moreover the results showed an accepted identity with the theoretical value of pressure in static case and accepted identity of the paths of stresses from experiments and calculated values of cases. Finally the results show the resulted sliding surface in all cases is non linear   and this disagrees with the Colomb Approximation, in the end, we have achieved an approximating forms for calculating the Lateral pressure on retaining walls in accordance with the case of displacement.